Harmonisation Of Sharia-Based Regional Regulations In Banjarmasin City With The Constitution: A Normative Juridical Study - Prasetia, Trenadi; Abdillah, Muhammad Torieq; Mahardika, Ahmad Gelora (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to examine the conformity of sharia-based regional regulations in Banjarmasin City with the 1945 Constitution of the Republic of Indonesia and to formulate harmonization strategies to ensure that such regulations remain consistent with the principles of the rule of law, legal pluralism, and the protection of constitutional rights. This research employs a normative juridical method using statutory, conceptual, and case approaches. The data were collected through a literature review of relevant legislation, sharia-based regional regulations in Banjarmasin City, and legal scholarship, and were analyzed qualitatively using systematic and constitutional interpretation. The findings indicate that several sharia-based regulations contain provisions that potentially conflict with constitutional principles, particularly freedom of religion, equality before the law, and non-discrimination. Although these regulations were enacted based on the aspirations of the local majority and intended to promote morality and public order, their implementation has not fully accommodated societal diversity and constitutional rights. This study proposes harmonization through substantive normative revisions, the application of inclusive legal principles, and the establishment of continuous evaluation and monitoring mechanisms. The results of this research are expected to contribute to policy formulation by local governments in developing regional regulations that are constitutional, equitable, and responsive to legal and social pluralism.